Photonic band gap effect and dye-encapsulated cucurbituril-triggered enhanced fluorescence using monolithic colloidal photonic crystals. (4th October 2019) - Vipin, V. V.; Chandran, Parvathy R.; M. Ramachandran, Animesh; Mohamed, A. P.; Pillai, Saju
Abstract : Enhanced fluorescence was achieved by tuning the photonic band gaps in colloidal photonic crystals and host–guest chemistry. Abstract : It is well known that enhanced fluorescence of dye molecules can be achieved by the formation of host–guest complexes that enhance the efficiency of chemical sensors, bio-imaging and photovoltaic devices. Herein, dual enhancement in fluorescence intensity was obtained by tuning three-dimensional (3D) periodic architectures of colloidal photonic crystals (CPCs) and host–guest chemistry. CPCs offer an appropriate platform with slow photon effects at the edges of a photonic band gap (PBG). These photons with decreased group velocity facilitate enhanced excitation and light extraction, which aid fluorescence enhancement; meanwhile, the host–guest chemistry of rhodamine B (RhB) with cucurbit[7]uril (CB7) decreases aggregation-caused quenching, which provides additional fluorescence enhancement. We demonstrated the augmentation of fluorescence intensity of a model dye, RhB, using size-tuned polystyrene (PS) CPC films where RhB forms an inclusion complex with the host, CB7. Compared to a planar PS film (control sample), over 150-fold fluorescence enhancement was achieved using the monolithic CPC films. Our strategy for generating dual enhanced fluorescence can stimulate the ultra-sensitive detection capabilities of fluorescence-based chemical and biochemical sensors, providing stronger signals and lower limits of detection.